Dual resistance to Flavobacterium psychrophilum and Myxobolus cerebralis in rainbow trout (Oncorhynchus mykiss, Walbaum). Issue 6 (8th March 2022) - Avila, Brian W.; Winkelman, Dana L.; Fetherman, Eric R.
Abstract: Aquatic pathogens are a major concern for fish hatchery production, fisheries management, and conservation, and disease control needs to be addressed. Two important salmonid pathogens are Myxobolus cerebralis and Flavobacterium psychrophilum that cause whirling disease and bacterial coldwater disease (BCWD), respectively. Innate disease resistance is a potential option for reducing disease‐related mortality in hatchery‐reared rainbow trout ( Oncorhynchus mykiss, Walbaum). Two experiments were conducted to assess pathogen resistance of first‐generation (F1) rainbow trout created by crossing M. cerebralis ‐ and F. psychrophilum ‐resistant strains. In the first experiment, we exposed two rainbow trout strains and one F1 cross to six treatments: control (no exposure), mock injection, F. psychrophilum only, M. cerebralis only, F. psychrophilum then M. cerebralis, and M. cerebralis then F. psychrophilum . Results indicated that the F1 cross was not resistant to either pathogen. In the second experiment, we exposed five rainbow trout strains and four rainbow trout crosses to F. psychrophilum . The second experiment indicated that at least one rainbow trout cross was F . psychrophilum ‐resistant. Achieving dual resistance may be possible using selective breeding but only some multigenerational strains are suitable candidates for further evaluation.